Therapeutic Innovations in Nanomedicine: Exploring the Potential of Magnetotactic Bacteria and Bacterial Magnetosomes - Yadav VK; Pramanik S; Alghamdi S; Atwah B; Qusty NF; Babalghith AO; Solanki VS; Agarwal N; Gupta N; Niazi P; Patel A; Choudhary N; et al. (International Journal of Nanomedicine)
Virendra Kumar Yadav,1,* Sheersha Pramanik,2,* Saad Alghamdi,3 Banan Atwah,3 Naeem F Qusty,3 Ahmad O Babalghith,4 Vijendra Singh Solanki,5 Neha Agarwal,6 Nishant Gupta,7 Parwiz Niazi,8 Ashish Patel,9 Nisha Choudhary,9 Rustem Zairov10,11 1Marwadi University Research Center, Department of Microbiology, Faculty of Sciences, Marwadi University, Rajkot, Gujarat, 360003, India; 2Department of Biotechnology, Bhupat and Jyoti Mehta School of Biosciences, Indian Institute of Technology Madras, Chennai, Tamil Nadu, 600036, India; 3Department of Clinical Laboratory Sciences, Faculty of Applied Medical Sciences, Umm Al-Qura University, Makkah, Saudi Arabia; 4Medical Genetics Department, College of Medicine, Umm Al-Qura University, Makkah, Saudi Arabia; 5Department of Chemistry, Institute of Science and Research (ISR), IPS Academy, Indore, India; 6Department of Chemistry, Navyug Kanya Mahavidyalaya, University of Lucknow, Lucknow, Uttar Pradesh, India; 7Department of Engineering and Medical Devices, River Engineering Pvt Ltd, Ecotech-III, Greater Noida, U.p., India; 8Department of Biology, Faculty of Education, Kandahar University, Kandahar, Afghanistan; 9Department of Lifesciences, Hemchandracharya North Gujarat University, Patan, Gujarat, 384265, India; 10Arbuzov Institute of Organic and Physical Chemistry, FRC Kazan Scientific Center RAS, Kazan, Russian Federation; 11Aleksander Butlerov Institute of Chemistry, Kazan Federal University, Kazan, Russian Federation*These authors contributed equally to this workCorrespondence: Virendra Kumar Yadav; Nisha Choudhary;, Email yadava94@gmail.com; nishanaseer03@gmail.comAbstract: Nanotechnology has emerged as a revolutionary domain with diverse applications in medicine, and one of the noteworthy developments is the exploration of bacterial magnetosomes acquired from magnetotactic bacteria (MTB) for therapeutic purposes. The demand for natural nanomaterials in the biomedical field is continuously increasing due to their biocompatibility and eco-friendly nature. MTB produces uniform, well-ordered magnetic nanoparticles inside the magnetosomes, drawing attention due to their unique and remarkable features. MTB and magnetosomes have gained popularity in cancer treatment and diagnosis, especially in magnetic resonance imaging. Distinctive features highlighted include advancements in extraction, characterization, and functionalization techniques, alongside breakthroughs in utilizing MTB-based magnetosomes as contrast agents in imaging, biocompatible drug carriers, and tools for minimally invasive therapies. The biocompatible nature, functionalizing of the surface of bacterial magnetosomes, and response to the external magnetic field make them a potential candidate for the theragnostic purpose of MTB and magnetosomes. In the present review, emphasis has been given to the foundation of magnetosomes at a genetic level, mass production of magnetosomes, etc. Further authors have reviewed the various functionalization methods of the magnetosomes for cancer treatment. Finally, the authors have reviewed the recent advancements in MTB and magnetosome-based cancer detection, diagnosis, and treatment. Challenges such as scalability, long-term safety, and clinical translation are also discussed, presenting a roadmap for future research exploiting MTBs and magnetosomes’ unique properties.Keywords: magnetotactic bacteria, magnetosomes, hyperthermia, gene therapy, nanomedicine